Pengembangan Motif Batik Papua Barat Dengan Sumber Ide Burung Kasuari - Alifia Ayu Pratiwi; Setyawan Setyawan (Ornamen, 2022)
The purposes of this creative process is to add a new variation of Papuan Batik which focusing on Cassowary bird as the point of interest in the pattern so that the immigrant people can get to know more about the unique fauna of Papua, Cassowary. The method used in this design process is the Colin Clipson design method, quoted by Prof. Dr. Nanang Rizali, MSD in his book which covers problem identification, design analysis, ctreative process, and in this designing process, the study of production also conducted to give  conclusion on how to improve West Papuan Batik pattern using the idea of Cassowary bird. Based on the results of survey and data analysis, 8 design was created using repeated technique. Those designs include the exploration of Cassowary as the main pattern, areca nut leaves as the supporting pattern and Asmat wood craving which give distinct contrast between Papuan Batik and Javanese Batik. The design will be realized in the form of cloth measuring 200cm x 100cm.